APLIKASI ABSENSI DIGITAL UNTUK KARYAWAN MENGGUNAKAN DETEKSI WAJAH PADA DESA BANGUNJAYA - Raihan Hari Dwiguna; A. Nurul Anwar; Ade Napila; Andrian Hidayat (Journal of Research and Publication Innovation, 2024)
Bangunjaya Village processes employee attendance by writing their names in the attendance book and signing it every day. If an employee is unable to come in or is sick, the employee will not carry out the attendance process. The number of reports submitted to the admin is the number of names of employees who have been absent or are listed in the absence book. Research methods that can be used in research on Digital Attendance Applications for Employees Using Face Detection using the Face Recognition method in Bangunjaya Village. Building digital attendance applications for employees using Android-based face detection in Bangunjaya Village, as a more sophisticated and reliable solution for optimizing the attendance process. Research has succeeded in implementing a digital solution in the form of an attendance application using facial detection using the Face Recognition method as a replacement for manual processes in Bangunjaya Village.